Smart Greenhouse Untuk Tanaman Cabai Menggunakan Konsep IoT Berbasis Fuzzy Logic - Ugan Endang; Irman Hariman (Journal Data Science, Technology, Informatics and Security, 2023)
In this work, the author created a Smart Greenhouse Application program for Chili Plants Using an IoT Design based on Fuzzy Logic, where the data presented are suitable and can be accounted for. In this application, there is real-time data about the conditions in a greenhouse with an IoT concept that works on information using Fuzzy Logic. To conceptualize the Smart Greenhouse Application for Chili Plants Using an IoT Design based on Fuzzy Logic, the author creates shapes by uml to work on data and data. The program of this application uses PHP, MySQL as the database, arduino program makes IoT designs and other parts that support the presentation of the data needed